Technical and economical assessment of thermo-mechanical extrusion pretreatment for cellulosic ethanol production - Yoo, Juhyun (Kansas State University, 2011)
The Renewable Fuel Standard (RFS) in the Energy Independence and Security Act of 2007 has set the goal of 36 billion gallons of annual ethanol production in the U.S. by 2022, which is equivalent to 17.5% of the current gasoline consumption in the U.S. However, corn ethanol is expected to plateau at a level of 7.3% of current gasoline consumption on an energy-equivalent basis. Thus, it is essential to utilize a variety of substrates including lignocellulosic biomass from perennial energy crops such as switch grass, crop residues such as corn and sorghum stover, and agri-industrial co-products such as soybean hulls and wheat bran. Lignocellulosic substrates have a recalcitrant nature and require a pretreatment step that is critical for efficient enzymatic hydrolysis of cellulose and hemicellulose to fermentable sugars. In this study, soybean hulls were used as a model substrate for cellulosic ethanol. A novel thermo-mechanical pretreatment process using extrusion was investigated and compared with two traditional pretreatment methods, dilute acid and alkali hydrolysis, with regard to structural changes in the lignocellulosic substrate, and glucose and ethanol yields. The effect of extrusion parameters, such as barrel temperature, in-barrel moisture and screw speed, on glucose yield from soybean hulls was determined. Optimum processing conditions were screw speed of 350 rpm, maximum barrel temperature of 80C and 40% in-barrel moisture content, resulting in 95% cellulose conversion to glucose. Compared with untreated soybean hulls, the cellulose to glucose conversion of soybean hulls increased by 69.5, 128.4 and 132.2% for dilute acid, alkali and thermo-mechanical pretreatments, respectively. Glucose and other hexose sugars such as mannose and galactose were effectively fermented by Saccharomyces cerevisiae, resulting in ethanol yields of 13.04–15.44 g/L. Fermentation inhibitors glycerol, furfural, 5-(hydroxymethyl)-2-furaldehyde (HMF) and acetic acid were found in the thermo-mechanically pretreated substrate, ranging in concentrations from 0.072–0.431, 0–0.049, 0–0.023 and 0.181–0.278 g/L, respectively, which were lower than those reported from acid hydrolyzed substrates. The economic feasibility of commercial cellulosic ethanol production processes employing dilute acid hydrolysis and thermo-mechanical pretreatment were compared using a system dynamics modeling approach. It was concluded that low feedstock cost and high sugar conversion are important factors that can make cellulosic ethanol production commercially viable. Thermo-mechanical pretreatment was a more promising technology as compared to dilute acid hydrolysis because of the lower capital and operating costs, and higher sugar conversion.
Keywords: Bioethanol; Extrusion; Pretreatment; Lignocellulosic; Economic analysis; Soybean hulls; Agriculture, General (0473); Alternative Energy (0363)